2019
DOI: 10.5902/2318133836102
|View full text |Cite
|
Sign up to set email alerts
|

O ciclo PDCA como proposta para uma gestão escolar eficiente

Abstract: A escola está inserida como componente da atual sociedade das organizações, sendo um dos componentes do macro sistema organizacional, o que sugere a necessidade de uma boa gestão para que se mantenha sustentável e competitiva. Assim, neste estudo, tem-se por objetivo sugerir o ciclo PDCA como proposta para uma gestão escolar eficiente. Para tanto, utilizou-se o método bibliográfico conceitual desenvolvido por Nascimento-e-Silva (2012), que consiste na formulação de questões norteadoras, coleta de dados em livr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 2 publications
0
9
0
19
Order By: Relevance
“…The application of this method allowed a) to delimit the conceptual scope of the research protocols, b) to identify the essential elements of the research protocols and c) to understand what are the steps for the elaboration of a research protocol. Through this construct, it appeared that the logic of execution of this methodological document is of the procedural type (Albuquerque, Morais, Lima, & Nascimento-e-Silva, 2018;Brito, Nascimento-e-Silva, Sores, & Soares, 2016;Silva, Oliveira, Sá Filho, & Nascimento-e-Silva, 2019), in which each step described in the protocol must be followed to ensure that the final objective of the research is reached in an unchallenged manner. The study demonstrated that the protocols should not be confused with research questionnaires, which have other techniques of implementation and their application is recommended for other purposes, more precisely in studies that seek to evidence the opinion of a certain population regarding the theme worked by researcher.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The application of this method allowed a) to delimit the conceptual scope of the research protocols, b) to identify the essential elements of the research protocols and c) to understand what are the steps for the elaboration of a research protocol. Through this construct, it appeared that the logic of execution of this methodological document is of the procedural type (Albuquerque, Morais, Lima, & Nascimento-e-Silva, 2018;Brito, Nascimento-e-Silva, Sores, & Soares, 2016;Silva, Oliveira, Sá Filho, & Nascimento-e-Silva, 2019), in which each step described in the protocol must be followed to ensure that the final objective of the research is reached in an unchallenged manner. The study demonstrated that the protocols should not be confused with research questionnaires, which have other techniques of implementation and their application is recommended for other purposes, more precisely in studies that seek to evidence the opinion of a certain population regarding the theme worked by researcher.…”
Section: Methodsmentioning
confidence: 99%
“…The research protocols follow a procedural logic, which in other words means that the researcher when successfully completing each phase will inevitably reach a result (Albuquerque et al, 2018;Brito et al, 2016;Silva et al, 2019). Here the mandatory elements that a research protocol must present will be presented.…”
Section: Elements Of Research Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma das etapas do processo gerencial é a função controle (SILVA et al, 2019). Esta função tem como finalidade garantir que os objetivos definidos sejam materializados a partir do uso de certos recursos utilizados na execução de uma ou mais estratégias, que são formas de fazer o que tem que ser feito, de materialização de objetivos.…”
unclassified